2022
DOI: 10.1016/j.ejvs.2021.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Traumatic Aortic Injury Management, a French TraumaBase Analytic Cohort

Abstract: WHAT THIS PAPER ADDSA complete analysis was performed of the clinical pathway from pre-hospital management to discharge and long term follow up of patients with blunt traumatic aortic injury (BTAI). Endovascular treatment is confirmed as the reference treatment growing to more than 90% of treated patients with a 18.3% complication rate. The time to diagnosis was longer for the more severe BTAI injuries, probably given the intensity of resuscitation required, suggesting a need to minimise delays in early manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, the diagnosis of this potentially fatal condition at an appropriate time is not always straightforward. On the other hand, early diagnosis, especially in severe cases, has been associated with a significant reduction in the risk of morbidity and mortality [ 10 ]. The initial evaluation almost always begins with an anteroposterior chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis of this potentially fatal condition at an appropriate time is not always straightforward. On the other hand, early diagnosis, especially in severe cases, has been associated with a significant reduction in the risk of morbidity and mortality [ 10 ]. The initial evaluation almost always begins with an anteroposterior chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of this TAI largely depends on the initial CT and clinical manifestations such as a hemorrhagic shock after injury. For acute BTAI, only about 20% of patients can make it to the hospital, and more than 40% die during their hospital stay ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of BTAI is crucial to reduce mortality rates, particularly in severely diseased patients. Boutin et al, in fact, in their multicenter retrospective study, found that the time to diagnosis increased with the severity of the aortic injury and the clinical severity of the patients [10].…”
Section: Diagnosismentioning
confidence: 97%